The Influence of Motivation and Work Stress on Employee’s Performance (A Case Study at PT. PLN (Persero) UPT Semarang) - Arva’ni Za’imil Ashiya; Sugiyanta - Sugiyanta; Suwardi - Suwardi (Admisi dan Bisnis, 2023)
This study aims to determine the motivation and work stress on the performance of employees of PT. PLN (Persero) UPT Semarang. Data collection methods used are through interviews, questionnaires and literature study. The number of samples in this study were 77 employees with the census method. The analytical method used is the validity and reliability test, classical assumption test, multiple linear regression test, t test, F test and the coefficient of determination test. The results showed that partially motivation and work stress have a significant positive effect on employee performance. Simultaneously, motivation and work stress have a significant effect on employee performance. Motivation has the greatest influence in improving employee performance